2004
DOI: 10.1016/j.cognition.2003.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Geometric determinants of human spatial memory

Abstract: Geometric alterations to the boundaries of a virtual environment were used to investigate the representations underlying human spatial memory. Subjects encountered a cue object in a simple rectangular enclosure, with distant landmarks for orientation. After a brief delay, during which they were removed from the arena, subjects were returned to it at a new location and orientation and asked to mark the place where the cue had been. On some trials the geometry (size, aspect ratio) of the arena was varied between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
159
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(178 citation statements)
references
References 75 publications
13
159
2
Order By: Relevance
“…Otherwise, orientation might depend on many types of cue, combining outside of the hippocampus in the head-direction circuit (43) and possibly by associative reinforcement. Thus, asymmetrical boundary geometry and distal cues combine to orient participants (44) [and place cell firing (45)] and can overshadow and block each other in doing so (8,9,46,47). Whether or not distal cues do block each other in determining orientation depends on many factors, including task instructions (O. Hardt, A. Humpbach, and L. Nadel, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, orientation might depend on many types of cue, combining outside of the hippocampus in the head-direction circuit (43) and possibly by associative reinforcement. Thus, asymmetrical boundary geometry and distal cues combine to orient participants (44) [and place cell firing (45)] and can overshadow and block each other in doing so (8,9,46,47). Whether or not distal cues do block each other in determining orientation depends on many factors, including task instructions (O. Hardt, A. Humpbach, and L. Nadel, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2012) found that the relative lengths of isolated walls are not used to locate hidden objects but that, instead, the distances of the walls are important, perhaps based neurophysiologically on boundary vector cells (discussed further below; Burgess, Jackson, Hartley, & O'Keefe, 2000;Hartley, Burgess, Lever, Caccuci, & O'Keefe, 2000;Lever, Burton, Jeewajee, O'Keefe, & Burgess, 2009; see also Hartley, Trinkler, & Burgess, 2004, for some relevant human behavioral data). These cells (found in rats) fire most when the animal is at a particular distance from a surface.…”
Section: Modularity Theorymentioning
confidence: 99%
“…" Regardless of what terms are used, the distinction between conditions and connections is important, partly because the human brain appears to acquire and store information about place (conditions) and movement (connections) in different modes. "These strategies [spatial thinking by associating landmarks and tracing routes] may be subserved by different cortical areas [in the brain]" (Aginsky et al 1997, 317; see also Burwell et al 2004;Ekstrom et al 2003;Ferguson and Hegarty 1994;Golledge et al 1995;Gouteux et al 2001;Hartley et al 2004;Newcombe et al 1998).…”
Section: Conditions and Connections: The Basic Facts Of Geographymentioning
confidence: 99%
“…Apparently it uses an interconnected system of at least three different brain areas that separately encode relative locations according to different frames of reference (Committeri et al 2004;Hartley et al 2004; and more than sixty other studies). One of those frames of reference is based on the geometric characteristics of everyday objects.…”
Section: Location: What Makes a Topic Geographic?mentioning
confidence: 99%